GSTM1 and GSTT1 Polymorphisms and the Risk of Prostate Cancer in a Caribbean Population of African Descent - Mallick, Stéphane; Romana, Marc; Blanchet, Pascal; Multigner, Luc (Urology, 2007)
To investigate whether the glutathione S-transferase polymorphisms GSTM1 and/or GSTT1 contribute to prostate cancer risk in a Caribbean population of African descent in Guadeloupe. We performed a hospital-based case-control study with 134 prostate cancer patients and 134 cancer-free, age-matched control subjects. Epidemiologic data were collected using a standard questionnaire. Logistic regression was used to estimate odds ratios (ORs) and compute confidence intervals (CIs). Genotypes were determined by multiplex polymerase chain reaction. The frequency of the GSTM1-positive genotype was 81% in patients and 73% in control subjects, with an adjusted OR of 1.4 (95% CI 0.7 to 2.5). The frequency of the GSTT1-positive genotype was 78% in patients and 63% in control subjects, with an adjusted OR of 2.6 (95% CI 1.4 to 4.9). A functional GSTT1 polymorphism may be associated with prostate cancer susceptibility in a Caribbean population of African descent.